Comparison of preoperative anti-infective preparations for extracapsular lens extraction - Harvey S. Uy, MD; Roslyn D. Rodriguez, MD; Jacinto U. Dy-Liacco, MD (Philippine Journal of Ophthalmology)
Objective: To investigate the effect of three preoperative anti-infective regimens on the sterility of anterior-chamber aspirates (ACA) in eyes undergoing extracapsular cataract extraction (ECCE).